180=2x+103-x+(180-(6x+7))

Simple and best practice solution for 180=2x+103-x+(180-(6x+7)) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 180=2x+103-x+(180-(6x+7)) equation:



180=2x+103-x+(180-(6x+7))
We move all terms to the left:
180-(2x+103-x+(180-(6x+7)))=0
We calculate terms in parentheses: -(2x+103-x+(180-(6x+7))), so:
2x+103-x+(180-(6x+7))
determiningTheFunctionDomain 2x-x+(180-(6x+7))+103
We add all the numbers together, and all the variables
x+(180-(6x+7))+103
We calculate terms in parentheses: +(180-(6x+7)), so:
180-(6x+7)
determiningTheFunctionDomain -(6x+7)+180
We get rid of parentheses
-6x-7+180
We add all the numbers together, and all the variables
-6x+173
Back to the equation:
+(-6x+173)
We get rid of parentheses
x-6x+173+103
We add all the numbers together, and all the variables
-5x+276
Back to the equation:
-(-5x+276)
We get rid of parentheses
5x-276+180=0
We add all the numbers together, and all the variables
5x-96=0
We move all terms containing x to the left, all other terms to the right
5x=96
x=96/5
x=19+1/5

See similar equations:

| 7c=4c+33 | | -155=7(-5x=2)+6 | | 5v+1=6v-17 | | -5+k/5=-3 | | 4c=c+54 | | -10x=340 | | 2w=w+48 | | (3/2)b+5=20−b | | 4v=v+78 | | 7(2r+1)=-91 | | V+78=4v | | 3x+3–x+2=x+5 | | 2(9g-5=62 | | -104=-8+8(a-4) | | 2s=s+80 | | 2.5-3.5x=8+4x-6 | | (-7x-6)(5x-12)=0 | | 7m+23=4 | | (2x-4)/(24)=(39)/(x+6) | | 5.9(x-16)+3.4x=4+9.3 | | 3x-x=4=4(2x+1) | | 9–3x=1+x | | a+8-4=2 | | 160000=-0.05x | | 4*2+42x+110=0 | | 23=8+2k+3k | | 8x+9x=-4 | | 5z+1=66 | | 7x+3=×-18 | | 5z+1=56 | | 7b=144 | | 5z÷1=66 |

Equations solver categories